2016
DOI: 10.1080/19376812.2015.1130636
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with and measuring informality in the proposed Urban Sustainable Development Goal

Abstract: A unique project by Mistra Urban Futures to test the draft targets and indicators of the proposed Urban Sustainable Development Goal (Goal 11) in five diverse cities in Europe, Africa, and Asia revealed numerous complexities and differences in data availability, potential accessibility, and relevance. Deploying the findings from Kisumu and Cape Town, we highlight the particular challenges posed by widespread urban informality. Similar issues apply across the global South. The targets and indicators rely on off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…Previous analyses of the SDG indicators already surfaced the need to account for informality [41]. In the context of the 100RC work, the city of Cape Town has called for more attention to the importance of informality through the 100RC Network Exchange in Addis Ababa in December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of the SDG indicators already surfaced the need to account for informality [41]. In the context of the 100RC work, the city of Cape Town has called for more attention to the importance of informality through the 100RC Network Exchange in Addis Ababa in December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In this diverse set of cities, the pilot study found that not one draft indicator was regarded as both important/relevant and easy to report on in terms of data availability in all the cities; and no city found the entire set of draft indicators under SDG 11 straightforward and important or appropriate Arfvidsson et al 2017;Patel et al 2017). The investigated indicators remained mostly unchanged when Agenda 2030 was adopted.…”
Section: Context To the Research Projectmentioning
confidence: 96%
“…In Cape Town, for example, the researcher has been embedded into the City of Cape Town's This project is a follow-up to a comparative pilot study conducted by Mistra Urban Futures in the first half of 2015 Arfvidsson et al 2017;Patel et al 2017), which tested the potential targets and indicators for the urban SDG (SDG 11) in five cities: Cape Town, Gothenburg, Kisumu, Greater Manchester and Bangalore. This forerunner study contributed to the 'Campaign for an Urban SDG' 3 (SDSN 2013; Simon et al 2016) and tested the data availability, relevance and appropriateness of the draft targets and indicators for SDG 11.…”
Section: Context To the Research Projectmentioning
confidence: 99%
“…Understandably, households are reluctant to invest precious resources in assets that cannot easily be moved. The need to understand and respond to the issues of informality in the urban context is a theme that is gaining welcome exposure as approaches to monitoring the Sustainable Development Goals, particularly SDG 11, are developed [30]. Our study suggests that such efforts need to be reflected in the measurement of vulnerability to ensure that programmes can be reliably targeted at those in most need.…”
Section: By Migration Status By Residencementioning
confidence: 93%